POVERTY REDUCTION AND SUSTAINABLE DEVELOPMENT IN NIGER DELTA REGION OF NIGERIA: STRATEGIES FOR COUNSELLING - A.D, OGHIAGBEPHAN, (IJRDO - Journal of Applied Management Science, 2016)
The Niger Delta region of Nigeria is richly endowed with huge resources of petroleum oil which is a major source of National income, yet the region is characterized by poverty. It is against this background that the present paper attempts to examine how poverty can be reduced particularly in respect to the people through skills acquisition in the region. Despite all the measures adopted by government at all levels to reduce poverty, a high percentage of Nigerians are still poor. The scourge seems unbolting as a result of the negative role of globalization in the economy of Nigeria, disparities in peoples income, gender imbalance as far as access to economic resources is concerned, disparities in access to health and education, corruption, neglect of agriculture among others. Be that as it may, the paper highlights some of the causes and effects of poverty in Niger delta region, discusses some approaches to poverty reduction, mentions some reduction strategies, looks at some of the problems that militated against previous National Poverty eradication programmes and finally the author proffers some recommendations that will help to reduce poverty in the Niger Delta Region of Nigeria.